Explore the Interactive Influence of EWOM Message Characteristics and Formats on Online Brand Outcomes in the Context of Twitter: A Comprehensive Model - Alqahtani, Abdulaziz; Sharma, Piyush; Kingshott, Russel (2023)
Social media has become a pivotal element in our daily communication lexicon, namely electronic word of mouth (EWOM), described as electronic communication where a broad audience can easily share or convey information among themselves. With the rapid rise in popularity and use of social media platforms and associated electronic spread of word of mouth (EWOM), many inquiries still need to be uncovered regarding their impact on customer interaction. This study aims to explore the interactive effects of message characteristics (valence and credibility) and message formats (textual, pictorial, video, and audio) on brand evaluation and online brand engagement using the elaboration likelihood model of persuasion (ELM). A causal research design was implemented through a webbased investigation utilising a fictitious brand's Twitter account created specifically for this study. The participants were randomly assigned to one of 16 conditions using a between-subject factorial design with a 2 (EWOM message valence: negative vs. positive) x 2 (EWOM message credibility: low vs. high) x 4 (message formats: textual, pictorial, video, and audio) factorial arrangement. We employed a quantitative method, executing the web experiment via an online survey to examine all hypotheses using data from a simple random sample (N=480) of Twitter users. We found that positive valence has a stronger impact on brand evaluation than negative valence and that credibility positively moderates (enhances) the effect of message valence on online brand evaluation. In addition, we found significant differences in the impact of valence (but not credibility) on brand evaluation across message formats. Lastly, brand evaluation fully mediates the EWOM message valence (not credibility) on online brand engagement.